Representasi Komunikasi Kepemimpinan dalam Film - Yuda Sudrajat; Firmansyah (UNISBA Press, 2023)
Abstract. One of the mass communication media (Mass Communication Media) that currently attracts a lot of public attention, one of which is film. Every film produced must display a message contained in it addressed to the audience, one of which is a message of representation of leadership communication or leadership. This study discusses how the representation of leadership communication in groups in the Korean drama film Big Mouth. The purpose of this study is to look at the level of reality, level of representation and level of ideology that represents leadership communication in the group contained in the Korean Drama film